2022
DOI: 10.3892/ol.2022.13230
|View full text |Cite
|
Sign up to set email alerts
|

Matrine exerts antitumor activity in cervical cancer by protective autophagy via the Akt/mTOR pathway in vitro and in vivo

Abstract: Matrine is a quinazoline alkaloid extracted from Sophora flavescens. The aim of the present study was to determine whether matrine can induce autophagy in the human HeLa and SiHa cervical cancer cell lines in vitro and in vivo. Cell viability assay was used to assess the suppressive effect of matrine and cisplatin on the proliferation of HeLa and SiHa cells. A total of 28 4-week-old female BALB/c nude mice were used for the in vivo study. Autophagy and protein expression were observed via transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…It is found that matrine inhibits the growth and induces apoptosis of pancreatic cancer cells (Xu et al, 2022). Matrine can promote the autophagy of cervical cancer cells through the Akt/mTOR signaling pathway and can be used as an autophagy inducer of cervical cancer (Zhang et al, 2022). Besides, matrine inhibits the proliferation and migration of colorectal cancer cells and promotes the apoptotic ability of cancer cells (Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is found that matrine inhibits the growth and induces apoptosis of pancreatic cancer cells (Xu et al, 2022). Matrine can promote the autophagy of cervical cancer cells through the Akt/mTOR signaling pathway and can be used as an autophagy inducer of cervical cancer (Zhang et al, 2022). Besides, matrine inhibits the proliferation and migration of colorectal cancer cells and promotes the apoptotic ability of cancer cells (Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…25 Matrine impaired the proliferation and evoked autophagy in cervical cancer cells by blocking the Akt/mTOR pathway. 26 Ren's team showed that Matrine could weaken the invasiveness and metastasis of breast cancer via suppressing EMT progression through ITGB1. 10 In our study, we also confirmed the anticancer effects of Matrine in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Matrine‐inhibited M2‐like macrophage polarization to block the metastasis of lung cancer cells 25 . Matrine impaired the proliferation and evoked autophagy in cervical cancer cells by blocking the Akt/mTOR pathway 26 . Ren's team showed that Matrine could weaken the invasiveness and metastasis of breast cancer via suppressing EMT progression through ITGB1 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The AKT/mTOR is an intracellular pathway that plays an important role in regulating cell proliferation and migration ( Markowitsch et al, 2022 ; Shao et al, 2022 ; Zhang et al, 2022 ). Thus, the Western blot was used to explore the potential molecular effects of LDOC1 on liver cancer in this study.…”
Section: Discussionmentioning
confidence: 99%